2022
DOI: 10.1016/j.amsu.2021.103235
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laparoscopic sleeve gastrectomy vs laparoscopic Roux-en-Y gastric bypass on weight loss in Egyptian patients with morbid obesity

Abstract: Background Bariatric surgical operation is taken into consideration to be the handiest remedy for extreme obesity. Durability is the main requirement for the broad usage of bariatric surgery. According to several factors, the present work tries to match the SG and RYGB techniques. Methods This is a retrospective work that studied 200 morbid obese patients randomized and categorized into two groups according to the treatment method: the laparoscopic sleeve gastrectomy (L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…As living standards improve, so does the proportion of obese people, 1 and because the complications associated with obesity significantly impact their lives, making weight loss a popular topic among obese individuals. Laparoscopic sleeve gastrectomy (LSG) is a new option for obese patients due to its significant weight loss and improved comorbidity, 2 however, the incidence of postoperative pulmonary complications (PPCs) is as high as 18% among obese patients. 3 The occurrence of PPCs prolongs hospital stays and increases mortality, 4 , 5 and without effective measures, this healthcare burden will increase as the number of obese patients undergoing surgery increases.…”
Section: Introductionmentioning
confidence: 99%
“…As living standards improve, so does the proportion of obese people, 1 and because the complications associated with obesity significantly impact their lives, making weight loss a popular topic among obese individuals. Laparoscopic sleeve gastrectomy (LSG) is a new option for obese patients due to its significant weight loss and improved comorbidity, 2 however, the incidence of postoperative pulmonary complications (PPCs) is as high as 18% among obese patients. 3 The occurrence of PPCs prolongs hospital stays and increases mortality, 4 , 5 and without effective measures, this healthcare burden will increase as the number of obese patients undergoing surgery increases.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of overweight and obesity is increasing worldwide and this has raised serious public health concerns. Epidemiologic studies have identified high body mass index (BMI) as a risk factor for a wide range of chronic diseases, including cardiovascular disease [ 1 , 2 ], musculoskeletal disorders [ 3 , 4 ], diabetes mellitus, chronic kidney disease [ 1 , 5 ], infertility [ 6 ], asthma [ 7 , 8 ], sleep apnea, and many cancers such as esophageal, colon, endometrial and gall bladder [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the prevalence of post-operative complications and the possibility of fatality [7], [8], some bariatric surgeons routinely use the reinforcement of SL. However, some authors found that SL reinforcement (SLR) is an unnecessary procedure and has no role in preventing these complications [8].…”
Section: Introductionmentioning
confidence: 99%